Modelling drift of cold-stunned Kemp's ridley turtles stranding on the Dutch coast [version 2; peer review: 2 approved] - Erik van Sebille; Darshika Manral; Mark de Boer; Ilse Bos (Open Research Europe, 2024)
Background Every few years, juvenile Kemp’s ridley turtles (Lepidochelys kempii) are stranded on the Dutch coasts. The main population distribution of this critically endangered species primarily inhabits the Gulf of Mexico and the east coast of the United States. This study focuses on five reports from the Netherlands between 2007 and 2022, where juvenile turtles were reported to strand alive during the winter, albeit in a hypothermic state. At ambient ocean temperatures between 10°C and 13°C, Kemp’s ridley turtles begin to show an inability to actively swim and remain afloat on the ocean’s surface, a condition termed ‘cold stunning’. Understanding their transport in cold-stunned state can help improve the rehabilitation process of stranded turtles. Methods Cold-stunned turtles are back-tracked as passive, virtual particles from their stranding location using Lagrangian flow modelling. This study investigates when and where these juvenile turtles cross the threshold temperatures between 10° C and 14° C before stranding by tracking the temperature along the trajectories. Results As expected, the simulations show the transport of the cold-stunned turtles via the English Channel. More surprisingly, the analysis suggests they likely experience cold-stunning in the southern North Sea region and encounter temperatures below 10°C for only a few days to up to three weeks, and below 12°C for up to a month before stranding. Conclusions The estimate of cold-stunned drift duration of the turtles provides additional knowledge about their health status at the time of stranding. Adherence to rehabilitation protocols for Kemp’s ridley and post-release monitoring are recommended to improve their long-term survival.